Experimental and theoretical P-V-T equation of state for Os2B3. Issue 1 (2nd January 2021) - Burrage, Kaleb C.; Lin, Chia-Min; Chen, Wei-Chih; Chen, Cheng-Chien; Vohra, Yogesh K.
ABSTRACT: Thermoelastic behavior of transition metal boride Os2 B3 was studied under quasi-hydrostatic and isothermal conditions in a Paris-Edinburgh cell to 5.4 GPa and 1273 K. In-situ Energy Dispersive X-ray diffraction was used to determine interplanar spacings of the hexagonal crystal structure and the P-V-T data were fitted to a 3rd Order Birch–Murnaghan equation of state with a temperature modification to determine thermal elastic constants. The bulk modulus was shown to be K0  = 402 ± 21 GPa when the first pressure derivative was held to K0 '  = 4.0 from the room temperature P-V curve. Under a quadratic fit α = α 0 + α 1 T − α 2 T − 2, the thermal expansion coefficients were determined to be α 0 = 1.862 × 10 − 5  K −1, α 1 = 0.841 × 10 − 9  K −2, and α 2 = − 0.525  K. Density functional theory (DFT) with the quasi-harmonic approximation (QHA) were employed to study Os2 B3, including its P-V-T curves, phonon spectra, bulk modulus, specific heat, thermal expansion, and the Grüneisen parameter. A good agreement between the first-principle theory and experimental observations was achieved, highlighting the success of the Armiento-Mattsson 2005 generalized gradient approximation functional employed in this study and QHA for describing thermodynamic properties of Os2 B3 .